2012
DOI: 10.2298/avb1203151g
|View full text |Cite
|
Sign up to set email alerts
|

Chronic physical stress changes gene expression of catecholamine biosynthetic enzymes in the adrenal medulla of adult rats

Abstract: In this study we examined how chronic forced running (CFR) affects the expression of catecholamine biosynthetic enzymes and cAMP response element-binding (CREB) in the adrenal medulla and the weight of adrenal glands of rats. Also, we examined how CFR and additional acute immobilization stress affect the expression of catecholamine biosynthetic enzymes in the adrenal medulla and the concentration of catecholamines and corticosterone (CORT) in the blood plasma. In this experiment we used as a model force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 68 publications
1
22
1
Order By: Relevance
“…In this work, animals exposed to CSITR are already prepared to manage the new situation evoked by a novel stressor and the exaggerated response is not necessary. Our results, together with In our previous study we showed that long-term isolation had induced a reduction gene expression of catecholamine biosynthetic enzymes in the adrenal medulla (Gavrilović et al 2008). Also, in the present study we have found that the CSITR has induced a reduction of TH and DBH mRNAs and protein levels in the adrenal medulla.…”
Section: Imm and Csitr+imm Treatmentssupporting
confidence: 89%
See 2 more Smart Citations
“…In this work, animals exposed to CSITR are already prepared to manage the new situation evoked by a novel stressor and the exaggerated response is not necessary. Our results, together with In our previous study we showed that long-term isolation had induced a reduction gene expression of catecholamine biosynthetic enzymes in the adrenal medulla (Gavrilović et al 2008). Also, in the present study we have found that the CSITR has induced a reduction of TH and DBH mRNAs and protein levels in the adrenal medulla.…”
Section: Imm and Csitr+imm Treatmentssupporting
confidence: 89%
“…Immobilization is frequently used as an additional acute stressor and considered as one of the most intensive stressors that significantly changes gene expression (Kvetnansky et al 2009). Our previous data showed that exposure of socially isolated rats to additional immobilization produced exaggerated responses in gene expression of catecholamine biosynthetic enzymes in the adrenal medulla (Gavrilović et al 2008). The response to novel additional acute immobilization stress might reveal the detailed mechanisms underlying the gene expression of catecholamine biosynthetic enzymes in the adrenal medulla in specific stress conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reverse transcription was performed employing Ready-To-Go You-Prime First-Strand Bead (Amersham Pharmacia Biotech, Uppsala, Sweden) and pd (N) 6 primer according to the manufacturer's protocol. Real-time RT-PCR assay was done exactly as previously described [21] . PCRs were performed in the ABI Prism 7,000 Sequence Detection System at 50 ° C for 2 min, 95 ° C for 10 min, followed by 40 cycles at 95 ° C for 15 s and 60 ° C for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…A reference, endogenous control, was included in each analysis to correct the differences in the interassay amplification efficiency and all transcripts were normalized to cyclophilin A (ID: Rn 00690933) expression. Western blot analysis was performed as previously described [21] . For measuring TH, DBH and PNMT protein levels, a monoclonal primary antibody against murine TH (monoclonal antibody against TH from mouse-mouse hybrid cells, clone 2/40/15, dilution 1: 5,000), anti-DBH (N-terminal) antibody, human (dilution 1: 1,000, Sigma) and polyclonal anti-PNMT primary antibody, and rabbit (dilution 1: 1,000, Protos Biotech Corp., New York, N.Y., USA), respectively, were used.…”
Section: Methodsmentioning
confidence: 99%